Comparação entre as técnicas tradicional e acelerada de Ponseti no tratamento do pé torto congênito - Sabrina Versuti Nunes (2018)
Introduction: The treatment of congenital clubfoot by the technique recommended by Ponseti presents good results. Objectives: To evaluate if the treatment of congenital clubfoot by means of manipulations of the foot and exchange of plaster twice a week (accelerated technique of Ponseti) is able to reduce the time of treatment and to maintain the results obtained by the traditional technique (exchange of the plaster once a week ). To determine if clinical variables such as type of childbirth, sex, laterality of involvement (right and / or left), gestational age at birth (prematurity) and number of plasters have repercussions on the treatment. Casuistry and method: The sample consisted of 16 children and 25 congenital clubfoot. Randomization was used to compose two groups. Group 1, performed the traditional Ponseti technique and group 2, performed the accelerated technique of Ponseti. Percutaneous tenotomy of the calcaneus tendon was required for correction of the equine structure to complete the treatment in all cases. The feet of the children were evaluated and classified by two independent examiners by photographic record, at the beginning of the treatment and after the correction of the equine, according to the parameters proposed by Pirani. To evaluate interobserver reliability, we used the Quadratic Method Cohen Kappa test. A descriptive analysis was also performed. Data were expressed as mean ± standard deviation. The level of significance was 5% (p <0.05). Qualitative association analyzes were performed using Fisher's exact test. Qualitative data were assessed by Students t and Mann-Whitney tests for unpaired samples. Stata for Mac software (version 12.0) was used. Results: The two groups of children were considered similar for clinical issues prior to treatment and there was moderate and excellent agreement between the examiners at the beginning and at the end of treatment, respectively. The comparison between the two groups of children showed that: in group 2 (accelerated Ponseti technique), there was a need for a greater exchange of plaster and fewer days of treatment compared to group 1 (conventional Ponseti technique), both with significant difference. The evolution of the treatment in the two groups, evaluated by the Pirani score, was similar and with good results. Conclusion: The use of the accelerated Ponseti technique, was able to perform the congenital clubfoot treatment at approximately 60% of the time and with a similar Pirani score compared to the traditional technique of Ponseti. Clinical variables such as type of childbirth, gender, laterality of involvement (right and / or left), gestational age at birth (prematurity) and number of plasters did not affect the treatment of the children of both groups.